The effect of video assistant referee (VAR) on match performance in elite football: A systematic review with meta-analysis - Li, M.; Wang, X.; Zhang, S. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2024)
The increased utilization of the video assistant referee (VAR) system in professional football matches has sparked academic interest, leading to investigations of its impact on various performance variables. This systematic review and meta-analysis sought to assess the impact of VAR on match performance in elite football competitions and determine its effects on diverse variables. We undertook a thorough search of electronic databases and conducted a meta-analysis using the statistical software R. The standardized mean difference (SMD) was employed to quantify the pooled effect of VAR on match performance variables, such as red cards, yellow cards, fouls, offsides, and playing times for both halves and the total game. The analysis included 12 studies, covering 10,088 matches from various elite football competitions. Homogeneity was found in the red cards group, whereas significant heterogeneity was noted in the other groups. VAR implementation correlated with a reduction in fouls (SMD = -0.187) and offsides (SMD = -0.216), indicating statistically significant decreases. Conversely, VAR led to an extension in match playing time, notably in first-half (SMD = 0.406), second-half (SMD = 0.517), and total playing time (SMD = 0.747), with all increases being statistically significant. Our findings indicate that VAR has a significant impact on match performance variables in elite football. Furthermore, the efficacy of VAR interventions differs among organizations and leagues, necessitating future research to ascertain whether VAR`s impact is universal or varies with specific competitions.